Mediatization(s) : theoretical conversations between Europe and Latin America - Scolari, Carlos Alberto, 1963- (Intellect, 2021)
Introduces the main theories and authors on mediatization from Europe and Latin America in the last two decades. It frames these theories within the context of communication and media theories, and maps the current field of mediatization focussing on the most recent and cutting-edge theoretical, methodological and empirical contributions.